Morphological Changes of Cisplatin-resistant Human Breast Cancer MCF-7 Cell Line - Puspita, Nanda Ayu; Bedford, Amy (International Journal of Integrated Health Sciences, 2017)
Objective: To evaluate morphological changes of breast cancer cell line MCF-7 following the development of acquired resistance towards cisplatin. Resistance towards anticancer agents still plays an important role in the breast cancer chemotherapy failure.Methods: The cisplatin resistant subline MCF-7/CisR was developed in-vitro by cultivating the parental cell line cisplatin-sensitive MCF-7 with raising concentration of cisplatin (from 0.01 to 2.3 µM) for four months. The cell morphology was observed by giemsa staining. Results: The resistance was shown by the increase of IC50 by 9 folds on MCF-7/CisR compared to the initial IC50 value of MCF-7. The change in cisplatin cytotoxic potency on the resistant cell line was accompanied by the morphological modification, including the enlargement of cell size, the increase of nucleus and cytoplasm ratio, and the increase of the number of microvesicular and cytoplasmic granules.Conclusions: This result has supported the underlying mechanism of cisplatin resistance, including the ability of the cells to decrease intracellular cisplatin concentration and repair DNA damage effects.